2020
DOI: 10.1021/acsenergylett.0c00912
|View full text |Cite
|
Sign up to set email alerts
|

A Nonflammable Electrolyte Enabled High Performance K0.5MnO2 Cathode for Low-Cost Potassium-Ion Batteries

Abstract: The application of a layered K0.5MnO2 cathode in potassium-ion batteries is limited by its poor cycling performance when charged above 4.0 V (vs K+/K), and the underlying mechanism for this electrochemical instability is still unclear. Here, it is discovered that ethylene carbonate (EC) will intercalate into the depotassiated K0.5MnO2, causing the exfoliation of the layered compound and the capacity decay under high charge cutoff voltage. When the carbonates are replaced with a nonflammable phosphate, the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 34 publications
0
77
1
Order By: Relevance
“…[18] In our previous work, a fire-retardant electrolyte using triethyl phosphate as its single solvent was reported to show much better performance on graphite than the conventional ethylene carbonate (EC) and diethyl carbonate (DEC) electrolyte, and this electrolyte can also work on a K 0.5 MnO 2 cathode with over 4 V charging potential. [19,20] This is a good sign that nonflammable electrolyte can be adopted to address the safety of PIBs, although no nonflammable electrolyte has achieved long-term calendar performance in graphite anode for PIBs so far. The success or failure of an electrolyte is normally attributed to the stability of the SEI.…”
mentioning
confidence: 99%
“…[18] In our previous work, a fire-retardant electrolyte using triethyl phosphate as its single solvent was reported to show much better performance on graphite than the conventional ethylene carbonate (EC) and diethyl carbonate (DEC) electrolyte, and this electrolyte can also work on a K 0.5 MnO 2 cathode with over 4 V charging potential. [19,20] This is a good sign that nonflammable electrolyte can be adopted to address the safety of PIBs, although no nonflammable electrolyte has achieved long-term calendar performance in graphite anode for PIBs so far. The success or failure of an electrolyte is normally attributed to the stability of the SEI.…”
mentioning
confidence: 99%
“…Guo and co‐workers [ 34 ] found that in KFSI–TEP electrolyte, K metal anode could achieve a stable plating/stripping with a small voltage hysteresis and a high average coulombic efficiency of 99.6% during 500 cycles. Guo and co‐workers [ 35 ] also confirmed that the average coulombic efficiency of K 0.5 MnO 2 (4.0 vs K + /K) in KFSI–TEP electrolyte could achieve more than 99.6% and retain 84% capacity even after 400 cycles. Moreover, compared with the EC/DEC electrolyte, the K 0.5 MnO 2 in TEP electrolyte could remain the original bulk structure during cycling process.…”
Section: Nonaqueous Electrolyte For Potassium‐ion Batteriesmentioning
confidence: 86%
“…replaced the flammable EC with fire‐retardant TEP in the potassium bis(fluorosulfonyl) imide (KFSI) salt‐based electrolyte, which not only improved the battery safety, but also eliminated the exfoliation of layered K 0.5 MnO 2 cathode caused by EC solvent co‐intercalation. [ 79 ] A graphite||K 0.5 MnO 2 full cell based on the optimized electrolyte delivered superior long‐term cycle performance with an average Coulombic efficiency of ≈99.81%. Liu et al.…”
Section: Non‐flammable Organic Liquid Electrolytesmentioning
confidence: 99%